Precision-Guided Minimally Invasive Neurosurgery: Anatomical Accuracy, Patient Selection, and Contemporary Challenges - Andrés Omar Triviño Pinto; Brian Alejandro Berdugo Vargas; Alejandra Mendoza Ortiz; Adrian Jhair Flores Equilea; Natalia Restrepo Hinestrosa; Luis Roberto Hernández Mercado; Erick Fernando Flores García; Mariana Lineth Orozco Ricardo; Giliana Paola Velasquez Londoño (IECCMEXICO, 2026)
Image-guided minimally invasive neurosurgery has transformed the management of intracranial lesions by integrating advanced imaging, neuronavigation, stereotactic planning, intraoperative visualization, and reduced surgical corridors. The objective of this study was to analyze the anatomical precision, patient-selection criteria, clinical outcomes, and current limitations associated with minimally invasive image-guided neurosurgical approaches. A structured integrative review based on the scientific method was conducted using evidence from PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar. The analysis included studies addressing neuronavigation, diffusion tensor imaging and tractography, intraoperative magnetic resonance imaging, intraoperative ultrasound, tubular and parafascicular approaches, neuroendoscopy, augmented reality, and laser interstitial thermal therapy. The reviewed evidence showed that intraoperative MRI can significantly increase complete resection rates in selected glioma patients, while intraoperative ultrasound and tubular approaches also demonstrate favorable resection outcomes in appropriately selected populations. Navigation systems showed mean target registration errors of approximately 2.5–2.6 mm, although their accuracy may progressively decrease because of brain shift and intraoperative anatomical deformation. Patient selection was strongly influenced by lesion depth, accessibility, proximity to eloquent structures, lesion size and geometry, previous treatments, neurological status, and expected therapeutic benefit. Current limitations include registration error, imaging artifacts, restricted operative maneuverability, learning curves, procedure-specific complications, cost, technological availability, and heterogeneity of the available evidence. Overall, image-guided minimally invasive neurosurgery can improve anatomical localization and support safer, function-preserving interventions when combined with rigorous patient selection and intraoperative adaptability. Its clinical value should not be defined exclusively by the size of the surgical corridor, but by the capacity to achieve adequate lesion control while minimizing unnecessary disruption of healthy neural structures.